Modulatory effects and structural alteration of gut microbiota by traditional Chinese medicine - Feng Jiarun; Wei Xiaoqian; Chen Jieru; Wang Zirui; Lu Li; Lin Xiukun; Jiang Mengxi; Bauer Rudolf; Xu Huanli (Elsevier, 2022)
Objective: Due to the multiple components of traditional Chinese medicine (TCM), the exact mechanisms of their effects on the human body remain unclear. This review aimed to summarize the TCM formulas that have modulatory effects on gut microbiota structure. Methods: Since TCM is usually taken orally, TCM can exhibit direct modulatory effects on gut microbiota. In recent years, a growing amount of research has focused on the regulatory effects of TCM on structural alteration of gut microbiota. PubMed, web of Science, China National Knowledge Infrastructure (CNKI), and Wanfang Data Knowledge Platform (Wanfang) were used to search related articles published in recent years. Results: In this review, we summarize the TCM formulas that have modulatory effects on gut microbiota structure according to their classification. Future directions of research on the regulation of gut microbiota by TCM and its application are also discussed. Conclusion: This review summarized the TCM formulas that have modulatory effects on gut microbiota structure and their interaction mechanisms, which may help to support the effective exploration and application of herbal medicines.